Desenvolvimento de método analítico para determinação dos principais adulterantes da cocaína em urina humana - Sena, Laís Cristina Santana (2016)
Cocaine is a stimulant that features a strong ability to cause dependence. Often adulterants are added to this drug in order to mimic its action or minimize its adverse effects. When there are other pharmacologically active components in the drug composition, severe problems can occur to users’ health, such as intoxication symptoms. Thus, the aim of this study was to develop a method for the determination of the main adulterants of cocaine (caffeine, levamisole, lidocaine, phenacetin, diltiazem, and hydroxyzine) in human urine. The high-performance liquid chromatography with a photodiode array detector and the dispersive liquid-liquid microextraction based on solidification of floating organic drop were used as analysis technique and as sample preparation technique, respectively. The reversed-phase chromatographic separation was obtained with a C18 column (250 x 4.6 mm; 5 μm; 80 Å) in gradient elution mode using acetonitrile-trifluoroacetic acid 0.026% (v/v) at 1 mL min-1 as mobile phase, at 25°C, and detection at 235 nm. The analysis time was 25 min. Under optimum conditions, human urine samples were alkalized with 0.5 mol.L-1 sodium phosphate buffer (pH 10) and added sodium chloride (20% m/v). Acetonitrile (150 μL) and 1-dodecanol (30 μL) were used as dispersive and extraction solvent, respectively. The method presented linear range of 312.5 – 3125 ng.mL−1 for caffeine and levamisole and 187.5 – 1875 ng.mL−1 for lidocaine, phenacetin, diltiazem, and hydroxyzine, with limit of quantification of 187.5 ng.mL-1 to lidocaine, phenacetin, diltiazem, and hydroxyzine and 312.5 ng.mL-1 for caffeine and levamisole. Recovery mean values were between 6.0 and 42.6%. The method showed good precision and accuracy, with within- and between-run relative standard deviation and relative error less than 15%. The samples were stable after freeze-thaw cycle and short-term room temperature stability tests. Additionally, this method was applied in samples of urine of five cocaine users and at least one adulterant was identified in all samples. It is expected that this method will contribute to the precision in the diagnosis of cocaine adulterants’ intoxication and to the proper planning of therapeutic measures.